The Depiction of Slavery in Butler's Kindred - Honsová, Adéla (Univerzita Pardubice, 2020)
This bachelor thesis deals with the portrayal of slavery in the novel Kindred written by Octavia Estelle Butler. The theoretical part focuses on the historical context of slavery in the U. S., briefly presents slave and neo-slave narratives as well as introduces Octavia E. Butler and the genre and themes of the novel. The primary aim of this thesis is to analyze slavery and its consequences portrayed in the novel.
Obraz otroctví v díle Kindred
Keywords: otroctví; literatura; novootrokářská povídka; Butler, Octavia Estelle; slavery; literature; neo-slave narratives; Butler, Octavia Estelle